Environmental reconstruction and biostratigraphy of late Middle Pleistocene lakeshore deposits at Schöningen. Issue 89 (December 2015) - Urban, Brigitte; Bigga, Gerlinde
Abstract: The Pleistocene sequence of Schöningen provides a key link between unglaciated and glaciated areas in western Central Europe and is an important point of reference for the subdivision of the glaciated late Middle Pleistocene. This locality yields paleoecological and geological evidence of at least four interglacial periods prior to the Holocene and younger than the Elsterian glaciation. The Pleistocene deposits at Schöningen are valuable archives of climate, landscape, and human evolution, containing outstanding information on past environmental changes and human adaptation. This paper presents paleoenvironmental and biostratigraphical results from the Middle Pleistocene archaeological lakeshore site of Schöningen, focusing on the so-called reference profile Schöningen 13 II of 2003. We discuss the lithological, palynological, and macrobotanical evidence and present a revised subdivision and reinterpretation of late phases of the Reinsdorf Interglacial.